Coil bobbin composed of high-strength polyethylene fiber reinforced plastics for a stable high-field superconducting magnet. - Yamanaka, A. (IEEE Transactions on applied superconductivity)
High-field superconducting solenoid magnets sometimes quench by wire motion induced by electromagnetic force. Fiber reinforced plastic [Dyneema fiber reinforced plastic (DFRP)] pipes composed of high-strength polyethylene fiber by filament winding method could be constructed so as to expand in the circumferential direction when cooled to low temperature with an appropriate selection of winding angle and shape of the pipes. In the case of a superconducting coil fabricated with a DFRP bobbin, it is expected that wire motions in high field are decreased by expansion of the coil bobbin. In this paper, tap voltage between both ends of the coils fabricated with DFRP bobbin and stainless steel (SUS) bobbin were measured with increasing current. The coil using SUS bobbin showed many sharp peaks in tap voltage induced by quick wire motions. In contrast, those using DFRP bobbin showed only a few small peaks. These results suggest that wire motions were constrained by DFRP bobbin. The training effects were observed in both cases.